Performance of Porous Breakwaters: Application of the BOUSS-2D Model - R Balaji (The Journal of Engineering Research, 2012)
The hydrodynamic performance of porous breakwaters was studied by numerical analysis to assess reflection and transmission characteristics. The finite-difference method on BOUSS-2D was used to test the efficiency of porous breakwaters. The effects of porosity on reflection and transmission characteristics under the action of regular waves were investigated. The wave elevation time histories obtained from the numerical study were compared to those measured during an experimental study, on the leeward and seaward sides of the porous breakwater and were found to be in close agreement. The reflection coefficient increases, whereas the transmission coefficient decreases with a decrease in the porosity. A model with a porosity of 5.9% showed a maximum reflection coefficient of about 0.7 and a minimum transmission coefficient of 0.3. The details of the numerical method, physical model, model setup and results are discussed in this paper.